The house in the pines : a novel - Reyes, Ana, 1982- (New York : Dutton, 2023)
This is the story of a house. The cabin lies deep in the woods, where the trees are so dense it's easy to miss. On the outside it might look like it's crumbling, crawling with weeds, but on the inside it's warm and cosy. A fire crackles in the fireplace. Dinner simmers on the stove. Maya once saw this cabin as an idyllic place, like a cottage from a fairy tale, but now she knows the danger that lurks beneath. The summer she visited the cabin was the summer her best friend Aubrey died. Now, another woman from Maya's hometown has died in the same strange, unexplained way, and Maya believes only she can save the next innocent girl. Guided by her fractured memory and a mysterious, unfinished book by her late father, Maya returns home to face the house in the pines and the man who waits there - the man she's tried so hard to forget.
Originally published: U.S.: Dutton.
Keywords: New England -- Fiction